Cell Phone Controlled Fingerprint Solenoid Door Lock Using Arduino And Hc-05 - Shivprasad, Lingampally; A. Vinitha,; S. Ravinder,; T. Himaja, (International Journal of Psychosocial Rehabilitation, 2019)
Now the whole world is in the grasp of COVID 19 and everyone is taking precautions wherever they can to prevent themselves from contracting this serious disease by following social distancing, wearing masks, using cashless transactions, and avoids touching anything to prevent the spread of germs. With the advent of technology, the normal locks are becoming things of the past and new biometric-based locks and RFID based locks are becoming more and more mainstream. Fingerprint-based locks and attendance record-keeping devices are used in most of the offices and colleges too but nowadays it is not advisable to do so due to this pandemic and so we are going to build a door lock by using a solenoid lock and control it using an android app over Bluetooth so that we don’t have to touch the fingerprint sensor at all and just use your own phones to control the lock. In this project, we are going to build a biometric lock using Arduino nano with Bluetooth Module. Solenoid lock, and Android phone. Apart from hardware, a mobile application is also used to scan and verify the fingerprint and send the confirmation ID to Arduino through Bluetooth. Here we will use Smart Phone Finger Print Sensor to lock and Unlock the Door lock. We know that, the entire globe is infected with Covid 19, and everyone is doing everything they can do avoid contracting this serious sickness by adhering to social segregation, wearing coverings, using credit-only exchanges, and refraining from contacting anything to prevent the spread of germs. With the advancement of technology, traditional locks are becoming relics of the past, while new biometric based locks and Radio Frequency Identification (RFID) – based locks are becoming increasingly in common.